ANALISA YURIDIS TERHADAP PENERAPAN GENTLEMAN AGREEMENT DALAM KERJASAMA USAHA (STUDI KASUS: 188/PDT.G/2017/PN.SMN): Rama Kresna Prasetya - admin, admin (Fakultas Hukum Universitas Islam Jakarta, 2018)
Agreements are activities that are common in people's lives to carry out activities related to buying and selling, lending and borrowing, work agreements and so on. Agreement can be in oral form and can be in written form. Oral agreements are usually born because they only require an agreement between the parties, which is used by a simple society, whereas written agreements are usually born in relatively modern societies relating to businesses whose legal relationships are more complex. As for the problems in this study, namely regarding legal protection of the parties who have bound themselves in the agreement and want to be canceled by a third party. Therefore this study also aims to find out about the legal protection provided by the Criminal Procedure Code to the parties who make an agreement in good faith. This research method uses the normative method, which focuses research on legal principles and examines and examines written regulations, in terms of knowing the binding force in the agreement. The conclusions of this study are: 1. The legal strength of the Gentleman Agreement, that the KUHPer has provided legal protection to all parties who made an agreement or an agreement based on good intentions. The legal strength of a gentleman agreement lies in the validity of the binding basis used by the parties that made it, because the positive law that exists does not provide restrictions regarding a business agreement must be made and stated in written form, except certain agreements stipulated in the law other laws which are derivatives or lex specialis from KUHper. An oral agreement or better known as a gentleman agreement as long as it is made on the basis of good intentions and remains in the corridor of Article 1320 of the Indonesian Criminal Code, the oral agreement has the same legal force because it has acted as a law for the parties that made it based on Article 1338 of the Indonesian Criminal Code or that better known as the principle of pacta sunt servanda. 2. The verification process on the gentleman agreement is basically that the Criminal Code does not specifically stipulate that the agreement must be made black and white.In an unwritten agreement, proof of an agreement between the parties is the main objective in seeking formal truth. In practice, those who want to prove that an agreement has been made on an unwritten agreement is to submit witnesses who are considered to have known, witnessed and heard the incident firsthand. In the process of listening to witness testimony, the parties still adhered to the principle of Unus Testis Nullus Testis, that is, the statement of one witness is not enough, and must be added with other evidence. The legal force between an unwritten and written agreement is equally strong. Oral agreement even if it is not written in written form, but if the agreement is based on good faith and has fulfilled the main elements of the applicable agreement, then the agreement is legal, and has binding legal force